Knowledge, attitudes, and practices among physicians and pharmacists toward antibiotic use in sepsis - Zhang, Jingmin; Shi, Haipeng; Xia, Yanmei; Zhu, Zhenghua; Zhang, Yaojun (Frontiers in Medicine, 2025)
BackgroundSepsis management in the Intensive Care Unit (ICU) presents a significant challenge within contemporary healthcare. The primary challenge lies in ensuring the timely and appropriate utilization of antibiotics. Inappropriate antibiotic use in sepsis management can result in a multitude of adverse outcomes. There has been insufficient focus on thoroughly understanding and resolving the issues related to the improper application of antibiotics in sepsis treatment by physicians and pharmacists. This gap in research is concerning, considering its potential implications for patient outcomes and public health. This study aimed to assess the knowledge, attitudes and practices (KAP) among physicians and pharmacists toward antibiotic use in sepsis.MethodsThis web-based cross-sectional study was conducted at Shanxi Bethune Hospital between June 2023 and October 2023. A self-designed questionnaire was developed to collect demographic information of physicians and pharmacists, and to assess their knowledge, attitudes and practices toward antibiotic use in sepsis.ResultsA total of 200 valid questionnaires were collected. Among the participants, 115 (57.5%) were female and 118 (59%) had experience with ICU patient management. The mean knowledge, attitudes and practices scores were 10.2 ± 1.14 (possible range: 0–12), 45.88 ± 4.00 (possible range: 10–50) and 48.38 ± 5.84 (possible range: 11–55), respectively. Multivariate logistic regression showed that attitudes (OR = 1.59, 95%CI: 1.34–1.87, p < 0.001), work experience of 15 years and above (OR = 7.17, 95%CI: 2.33–22.0, p = 0.001) were independently associated with proactive practices. For physicians, the structural equation model (SEM) demonstrated that attitudes directly affects practices, as indicated by a path coefficient of 0.91 (p < 0.001). For pharmacist, SEM showed that knowledge directly affect attitudes, with a path coefficient of 0.75 (p < 0.024), moreover, attitudes directly affect practices, with a path coefficient of 0.87 (p < 0.001).ConclusionThe findings revealed that physicians and pharmacists have sufficient knowledge, active attitudes, and proactive practices toward the antibiotic use in sepsis. Nonetheless, the findings also reveal the persistence of certain misconceptions, alongside notable shortcomings in both attitudes and practices. Comprehensive training programs are imperative for enhancing the practices of physicians and pharmacists in this field.